Escherichia coli clonal group A causing bacteraemia of urinary tract origin. (12th July 2012) - Skjøt‐Rasmussen, L.; Olsen, S. S.; Jakobsen, L.; Ejrnæs, K.; Scheutz, F.; Lundgren, B.; Frimodt‐Møller, N.; Hammerum, A. M.
Abstract Escherichia coli clonal group A (CgA) causes disease in humans. This is the first study investigating the prevalence of CgA among E. coli from non‐urine, extraintestinal infections in a northern European country. E. coli blood (n = 196) and paired urine (n = 195) isolates from the same patients with bacteraemia of urinary tract origin were analysed. The isolates were collected from January 2003 through May 2005 at four hospitals in Copenhagen, Denmark. Pulsed‐field gel electrophoresis (PFGE) patterns, antimicrobial resistance and patient characteristics were determined for all CgA isolates; presence of virulence‐associated genes (VAGs) and serotypes were determined for the blood CgA isolates. Thirty blood isolates (15%) belonged to CgA. CgA blood isolates were associated with female patients and sulfamethoxazole‐trimethoprim resistance and they harboured a distinctive VAG profile. The blood and urine isolates from each pair were found to be related in 26 of 27 CgA blood/urine pairs, confirming a urinary tract origin of infection. Furthermore, a relationship between the PFGE patterns of CgA blood/urine isolates and CgA isolates from UTI patients in general practice and a CgA isolate from a community‐dwelling human reported previously, was found, suggesting a community origin of CgA. The finding of CgA strains in 15% of the E. coli bloodstream infections with a urinary tract origin in Denmark suggests that CgA constitutes an important clonal lineage among extraintestinal pathogenic E. coli. A reservoir of this pathogenic E. coli group in the community causing not only UTI but also more severe infections such as bacteraemia has implications for public health.